Transfers among Divorced Couples: Evidence and Interpretation - Weiss, Yoram; Willis, Robert J. (Journal of Labor Economics, 1993)
An analysis of the economic impact of divorce settlements in the United States is presented using data for a white cohort taken from the National Longitudinal Study of the High School Class of 1972. "The effects of spouses' incomes on the divorce transfer are estimated and used to simulate the welfare effects of divorce on husbands, wives, and children under alternative assumptions about marriage contracts and the ability of a couple to continue coordinating resources in the aftermath of divorce. We find a positive (negative) relationship between divorce transfers and the growth of husband's (wife's) earnings during marriage. The estimated expenditure on children in the divorce state is only half the accustomed level during marriage."